Age at onset in Huntington's disease: effect of line of inheritance and patient's sex. - Roos, R A (1991)
The Leiden Roster for Huntington's disease (HD) contained data on 2617 cases up to July 1988. The age at onset (AO) was known in 1084 cases and in 1020 of these both their AO and the sex of the affected parent was known. The mean AO was higher for females than for males and higher for maternal than for paternal cases. However, in the group born before 1925 only females with maternal inheritance had a higher mean AO. Data on influence of sex and line of inheritance were present for the grandparents as well as for the great grandparents. Influence of the line of inheritance from the grandparents was particularly present for the grandmother-father (MP) lineage; regarding the great grandparents a significant difference was found between the MPM and PMP lineage. The results obtained for juvenile HD cases were comparable to those previously published. In late onset cases (over 50 years) no maternal preponderance in inheritance was found.